Functional Properties of Chlorella vulgaris, Colostrum, and Bifidobacteria, and Their Potential for Application in Functional Foods - Ivana Hyrslova; Gabriela Krausova; Jana Smolova; Barbora Stankova; Tomas Branyik; Hana Malinska; Martina Huttl; Antonin Kana; Ladislav Curda; Ivo Doskocil (Applied Sciences, 2021)
The market for new functional foods and food supplements is rapidly evolving, with a current emphasis on using natural sources. Algae, probiotics, and colostrum are rich sources of nutrients and bioactive compounds with positive effects on human and animal health. To determine the potential for developing new functional foods combining these components, we evaluated their synergistic effects. We assessed the growth of selected bifidobacteria in a medium supplemented with Chlorella vulgaris and its immunomodulatory and cytotoxic effects on the human peripheral mononuclear cells and colon cancer cell lines Caco-2 and HT29. The hypocholesterolemic effects of Chlorella powder and bovine colostrum fermented by Bifidobacterium animalis subsp. lactis BB12® on lipid metabolism in rats fed a high-fat diet were also determined. Chlorella addition promoted Bifidobacteria growth, with significantly increased inflammatory cytokine (TNF-α and IL-6) levels following 1.0% (w/v) Chlorella stimulation. Rats fed diets containing fermented colostrum with 0.5% (w/v) added Chlorella powder exhibited significantly decreased triglyceride, very low-density lipoprotein, and alanine and aspartate aminotransferase levels, compared to those of the control group. These results support that C. vulgaris is not cytotoxic in intestinal cell models and affords prebiotic and immunomodulatory effects, as well as synergistic triglyceride-lowering effects with bovine colostrum and B. animalis subsp. lactis BB-12.